2013
DOI: 10.1159/000346799
|View full text |Cite
|
Sign up to set email alerts
|

Functional Polymorphism in the Neuropeptide Y Gene Promoter (rs16147) Is Associated with Serum Leptin Levels and Waist-Hip Ratio in Women

Abstract: Objective: The neuropeptide-Y (NP-Y) gene is a strong candidate gene in the pathophysiology of obesity-linked behavior, and several single-nucleotide polymorphisms of NP-Y have already been linked to body weight and appetite. However, the results from current studies remain inconclusive. The aim of the present study was to test whether a certain functional genetic variant (SNP rs16147) in the NP-Y promoter gene is associated with serum leptin levels and body fat distribution. Method: We genotyped and measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 88 publications
0
16
0
1
Order By: Relevance
“…Human and animal studies suggest that adiposity-induced leptin increase and subsequent leptin resistance would affect these transmitters, causing or worsening asthma symptoms. This relates both to orexigenic neuropeptides such as neuropeptide Y (114)(115)(116)(117)(118)(119)(120) , endocannabinoids (121,122) , endogenous opioids (123)(124)(125)(126) ; and anorexigenic neuropeptides such as tachykinins and its most studied members substance P (127)(128)(129)(130)(131)(132) , α-melanocyte-stimulating hormone (133)(134)(135) , corticotropin-releasing factor (136)(137)(138)(139)(140)(141) and serotonin (142)(143)(144)(145)(146)(147)(148)(149)(150) . Altogether, it suggests that these peptides can modulate asthmatic inflammation among obese patients.…”
Section: Possible Linksmentioning
confidence: 99%
“…Human and animal studies suggest that adiposity-induced leptin increase and subsequent leptin resistance would affect these transmitters, causing or worsening asthma symptoms. This relates both to orexigenic neuropeptides such as neuropeptide Y (114)(115)(116)(117)(118)(119)(120) , endocannabinoids (121,122) , endogenous opioids (123)(124)(125)(126) ; and anorexigenic neuropeptides such as tachykinins and its most studied members substance P (127)(128)(129)(130)(131)(132) , α-melanocyte-stimulating hormone (133)(134)(135) , corticotropin-releasing factor (136)(137)(138)(139)(140)(141) and serotonin (142)(143)(144)(145)(146)(147)(148)(149)(150) . Altogether, it suggests that these peptides can modulate asthmatic inflammation among obese patients.…”
Section: Possible Linksmentioning
confidence: 99%
“…Olza et al [21] found similar results concerning rs16147 in a pediatric population. Moreover, no significant associations were reported by other authors in adult populations [19,22]. …”
Section: Discussionmentioning
confidence: 67%
“…Mutschler et al [19] have shown that the rs16147 SNP is significantly associated with waist-to-hip ratio and serum leptin levels only in females. These results demonstrate that the NPY gene also accounts for the body fat mass distribution measured as waist-to-hip ratio, and they also reveal a gene-by-sex interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies in adults are scarce. For example, Mutschler et al [30] showed that this genetic variant of the NPY gene is significantly associated with the waist-to-hip ratio. However, a lack of association was reported in another adult sample [31].…”
Section: Discussionmentioning
confidence: 99%